An Evaluation of Parent-Produced Video Self-Modeling to Improve Independence in an Adolescent With Intellectual Developmental Disorder and an Autism Spectrum Disorder: A Controlled Case Study. (July 2015) - Allen, Keith D.; Vatland, Christopher; Bowen, Scott L.; Burke, Raymond V.
We evaluated a parent-created video self-modeling (VSM) intervention to improve independence in an adolescent diagnosed with Intellectual Developmental Disorder (IDD) and Autism Spectrum Disorder (ASD). In a multiple baseline design across routines, a parent and her 17-year-old daughter created self-modeling videos of three targeted routines needed for independence in the community. The parent used a tablet device with a mobile app called "VideoTote" to produce videos of the daughter performing the targeted routines. The mobile app includes a 30-s tutorial about making modeling videos. The parent and daughter produced and watched a VSM scene prior to performing each of the three routines in an analogue community setting. The adolescent showed marked, immediate, and sustained improvements in performing each routine following the production and implementation of the VSM. Performance was found to generalize to the natural community setting. Results suggest that parents can use available technology to promote community independence for transition age individuals.